2019
DOI: 10.1002/clc.23282
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association between plasminogen activator inhibitor‐1 rs1799889 polymorphism and venous thromboembolism: Evidence from a comprehensive meta‐analysis

Abstract: BackgroundAssociation between plasminogen activator inhibitor‐1 (PAI‐1) rs1799889 polymorphism and venous thromboembolism (VTE) were explored by many previous studies, yet the findings of these studies were conflicting.Hypothesis PAI‐1 rs1799889 polymorphism may serve as a genetic marker of VTE. We aimed to better clarify the relationship between PAI‐1 rs1799889 polymorphism and VTE in a larger combined population by performing a meta‐analysis.MethodsLiteratures were searched in Pubmed, Embase, Web of Science,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…The SERPINE1 -675 4G/5G minor allele frequencies detected in our study (0.53-0.56) are slightly higher than those reported in patients with VTE from Germany (0.44-0.49) and France (0.47) and similar to the values observed in the United Kingdom (0.53) [10]. To our knowledge, we are the first to show Polish data on these genetic variants in VTE patients.…”
Section: Robust Data Demonstrated No Relationship Between Both Mthfr ...supporting
confidence: 77%
“…The SERPINE1 -675 4G/5G minor allele frequencies detected in our study (0.53-0.56) are slightly higher than those reported in patients with VTE from Germany (0.44-0.49) and France (0.47) and similar to the values observed in the United Kingdom (0.53) [10]. To our knowledge, we are the first to show Polish data on these genetic variants in VTE patients.…”
Section: Robust Data Demonstrated No Relationship Between Both Mthfr ...supporting
confidence: 77%
“…Other coagulation system polumorphisms such as FXIII V34L polymorphism are less studied, but some studies show their potential for thrombosis risk evaluation [ 13 ]. As for the fibrinolysis PAI-1 polymorphism may serve as one of the predisposing factors of VTE [ 14 ]. Platelet glycoprotein polymorphisms such as) platelet GP Ia/IIa ITGA2 gene polymorphism (rs1126643), platelet GP IIb/IIIa ITGB3 gene polymorphism (rs5918), platelet GP Ib GP1BA gene polymorphism (rs6065), platelet GPVI GP6 gene polymorphism (rs1613662) were associated with myocardial infarction, coronary disease or VTE [ 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…PAI-1 rs1799889 4G/5G polymorphism (4G vs. 5G) has been associated with an increased risk of DVT, MI and ischemic stroke. 54) 55) 56) …”
Section: Racial Differences In Thrombogenicity Componentsmentioning
confidence: 99%
“…The significant linkage of PAI-1 rs1799889 polymorphism (4G vs. 5G) to the risks of DVT, CAD and ischemic stroke was more prominent in the Asian population. 55) 56) Limited studies have also identified lower levels of circulating protein C and protein S, and endogenous anticoagulants in African Americans. 59) 60) …”
Section: Racial Differences In Thrombogenicity Componentsmentioning
confidence: 99%